UNDERSTANDING INTERNAL BRANDING IMPACT ON FINANCIAL PERFORMANCE THROUGH CORPORATE CULTURE - Rusmin, Natasha; Kuslina, Boedi Hartadi (Jurnal Administrasi Bisnis, 2025)
This study examines hot internal branding impacts the financial performance of a company in Bandung, focusing on employees as brand ambassadors who embody and communicate organizational values. While branding is often see as externally driven, internal branding cultivates brand-aligned behaviours, enhancing intangible assets such as reputation, loyalty, and culture. A qualitative approach was used to gathered data through combining ethnographic through observation, analysis of some digital metrics from social media and web traffic, and document analysis from company’s surveys and financial data. Findings indicate that internal branding programme strengthen employees’ engagement which in turn impact financial performance of the company. Although internal branding investment may not yield immediate ROI, it strengthen brand equity, marketing efficiency, and long term profitability, It is reflected in ROE and intangible-based ROA. The study provides insights into branding as well as human resources literatures. And, it offering practical implication for business in handling internal branding to long-term organizational performance enhancement.